2011
DOI: 10.1007/s00253-011-3731-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching in brackish waters—effect of chloride ions on the acidophile population and proteomes of model species

Abstract: High concentrations of chloride ions inhibit the growth of acidophilic microorganisms used in biomining, a problem particularly relevant to Western Australian and Chilean biomining operations. Despite this, little is known about the mechanisms acidophiles adopt in order to tolerate high chloride ion concentrations. This study aimed to investigate the impact of increasing concentrations of chloride ions on the population dynamics of a mixed culture during pyrite bioleaching and apply proteomics to elucidate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 39 publications
2
54
1
Order By: Relevance
“…In another study, At. caldus cultures grown on elemental sulfur with 7 g L −1 NaCl for two weeks had planktonic cell densities 72% of those in cultures grown without added NaCl (Zammit et al, 2012), an estimate somewhat higher than the 42% obtained for the 5 g L −1 test in the present study. No other data on the sodium chloride tolerance of At.…”
Section: Effects Of Anions On Tetrathionate Oxidationcontrasting
confidence: 64%
“…In another study, At. caldus cultures grown on elemental sulfur with 7 g L −1 NaCl for two weeks had planktonic cell densities 72% of those in cultures grown without added NaCl (Zammit et al, 2012), an estimate somewhat higher than the 42% obtained for the 5 g L −1 test in the present study. No other data on the sodium chloride tolerance of At.…”
Section: Effects Of Anions On Tetrathionate Oxidationcontrasting
confidence: 64%
“…This capability was also reported from alkaliphilic, heterotrophic microorganisms (Willscher and Bosecker 2001 ), and more recently from some halotolerant actinobacteria such as genera Nocardiopsis (Schippers et al 2002 ). The growth of acidophilic microorganisms are chloride-dependent and are inhibited in presence of high concentration of this ion (Zammit et al 2012 ), thus the halophilic and halotolerant actinobacteria are of special interest due to their ability to thrive in high concentration of NaCl allowing to take advantage of seawater for prospective biomining techniques in drought affected environments. …”
Section: Heavy Metal Bioremediation and Biomining By Halophilic And Hmentioning
confidence: 89%
“…Chloride ion inhibition was observed when sodium chloride was added. Zammit et al also found that elevated chloride levels in leach solutions were inhibitory to iron-and sulfur-oxidizing microorganisms [17]. Iron (II) oxidation rate slowed down obviously while the time needed to reach the .…”
Section: Effect Of Ph and C àmentioning
confidence: 97%